SAM transmethylation pathway and adenosine recycling to ATP are essential for systemic regulation and immune response - Nedbalová, Pavla; Kaislerova, Nikola; Chodakova, Lenka; Moos, Martin; Doležal, Tomáš (eLife, 2025)
During parasitoid wasp infection, activated immune cells of Drosophila melanogaster larvae release adenosine to conserve nutrients for immune response. S-adenosylmethionine (SAM) is a methyl group donor for most methylations in the cell and is synthesized from methionine and ATP. After methylation, SAM is converted to S-adenosylhomocysteine, which is further metabolized to adenosine and homocysteine. Here, we show that the SAM transmethylation pathway is up-regulated during immune cell activation and that the adenosine produced by this pathway in immune cells acts as a systemic signal to delay Drosophila larval development and ensure sufficient nutrient supply to the immune system. We further show that the up-regulation of the SAM transmethylation pathway and the efficiency of the immune response also depend on the recycling of adenosine back to ATP by adenosine kinase and adenylate kinase. We therefore hypothesize that adenosine may act as a sensitive sensor of the balance between cell activity, represented by the sum of methylation events in the cell, and nutrient supply. If the supply of nutrients is insufficient for a given activity, adenosine may not be effectively recycled back into ATP and may be pushed out of the cell to serve as a signal to demand more nutrients.
Keywords: SAM transmethylation pathway; adenosine signaling; privileged immunity; S-adenosylhomocysteinase; adenosine kinase; adenylate kinase